Role of Renin-Angiotensin-Aldosterone System in Metabolic Syndrome and Obesity-related Hypertension - Kamide, Kei (Current Hypertension Reviews, 2013)
Several recent clinical trials show that blocking agents of the renin-angiotensin-aldosterone system (RAAS) reduce cardiovascular events in patients with metabolic syndrome based on insulin resistance and obesity, especially accumulated visceral fat. Our laboratory has focused on the relationship between the vascular RAAS and the action of insulin on the vasculature. We first revealed that the addition of insulin to cultured vascular smooth muscle cells (VSMC) markedly increases angiotensinogen and angiotensin II (Ang II) expression and production. Insulin addition also induces VSMC growth that is inhibited by the blockade of the RAAS by either ACEI or ARB which suggests a role for the RAAS in insulin-mediated growth. Insulin has a quite different effect on cultured vascular endothelial cells (EC) as it reduces angiotensinogen and renin expression. However, insulin added to EC induces a marked activation of ACE and the activated ACE promotes the conversion of Ang I to Ang II and cell growth under conditions of high insulin concentration. Ang II induces the progression of atherosclerosis through the production of oxidative stress that blocks insulin signaling and accelerates atherosclerosis. In this paper, we attempt to clarify the relationship between insulin resistance, the RAAS, and oxidative stress in vascular tissues to mimic in vivo conditions found in patients with metabolic syndrome and obesity-related hypertension as previously I reviewed in “Current Hypertension Reviews” in 2010 [1]. In addition, I update the relationships between vascular RAAS and insulin resistance for the last 4 years. JSH-2014 [2] states that the target goals of blood pressure (BP) for diabetes patients is lower than 130/80 mmHg, whereas updated JNC 8 [3] and ESH-ESC 2013 [4] recommends the target BP was changed to <140/90 mmHg for hypertensive patients with diabetes. Patients with diabetes and hypertension have reduced mortality as well as improved cardiovascular and cerebrovascular outcomes with treatment to a goal SBP < 150 mm Hg, but no randomized controlled trials support a goal <140/90 mm Hg. Despite this, the panel opted for a conservative recommendation in patients with diabetes and hypertension, opting for a goal level of <140/90 mm Hg in adult patients with diabetes and hypertension rather than the evidence based goal of <150/90 mm Hg [3, 5]. JSH-2014 recommends that the first choice of antihypertensive medication should be RAAS blockers such as ACE inhibitor or ARB. For the last several years, several large cohort clinical studies using ACEI and ARB have shown more favorable effects, but aldosterone receptor inhibitor (mineral corticoid receptor inhibitors; MR inhibitors) and Renin Inhibitors have been withdrawn. Some studies showed the strong support to use these medications for diabetic patients. This review will discuss the relationships between vascular RAAS and insulin resistance in patients with hypertension and diabetes as previously reviewed with new updated findings for the last 4 years, and clinical implications based on updated JNC-8, ESH-ESC2013 and JSH-2014.
Keywords: aldosterone receptor blockers